High-Temperature Short-Time Preserves Human Milk's Bioactive Proteins and Their Function Better Than Pasteurization Techniques With Long Processing Times - Kontopodi, Eva; Boeren, Sjef; Stahl, Bernd; van Goudoever, Johannes B.; van Elburg, Ruurd M.; Hettinga, Kasper (Frontiers in Pediatrics, 2022)
Donor human milk is generally processed by holder pasteurization (HoP) at 62.5°C for 30 min. This temperature-time combination is sufficient for eliminating pathogens in donor milk, but also negatively affects several bioactive milk components. Long heating up times may further affect the bioactive properties of pasteurized milk. High-Temperature-Short-Time (HTST), a treatment with shorter processing times (72°C for 15 sec), was investigated as a suitable alternative to HoP. In addition, pasteurization methods that follow the same temperature regime but with varying heating up times were compared. The effects of these methods on the levels and functionality of immunoglobulin A, lactoferrin, lysozyme and bile salt-stimulated lipase, were evaluated with LC-MS/MS-based proteomics and activity assays. HoP, a treatment with long processing times, times, caused the highest reduction in all proteins studied (reduced by 50-98%). Compounds such as lactoferrin and bile salt-stimulated lipase that are more sensitive to heat treatments were better retained with HTST, but their levels and functionality were still significantly lower than those of untreated donor milk (52% and 81% reduction of LTF and BSSL activity, respectively). Our findings showed that a treatment with considerably shorter processing times, such as HTST, may reduce the thermal damage caused to the bioactive proteins compared to HoP, without affecting safety. Since the vast majority of the donor human milk banks that are currently operating on a global level apply HoP to donor milk, our findings may provide relevant information for the optimization of donor milk processing.